Hubungan Dukungan Keluarga, Sumber Informasi dan Peran Petugas Kesehatan Dengan Perilaku Pemberian Kolostrum Pada Bayi Baru Lahir di Puskesmas Cimanggu Kecamatan Cibeber Kabupaten Cianjur Tahun 2023 - Sulastri Sulastri; Salfia Darmi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Introduction: Colostrum is a part of breast milk (ASI) which has a characteristic yellowish liquid that comes out on the first to the third day after giving birth. Colostrum contains 10-17 times more immune substances than mature milk, so it is very good to give because it functions to form the baby's antibodies. Objective: To determine maternal knowledge, family support relationships, sources of information, the role of health workers, maternal behavior and how to provide colostrum by giving colostrum to newborns at the Cimanggu Community Health Center, Cibeber District, Cianjur Regency in 2023. Method: The research method used is descriptive with Cross Sectional Study approach. The sample in this study was postpartum mothers on days 1-4 with a total of 30 samples. This sample was taken using a purposive sampling method and the measuring instrument used was a questionnaire. Results: This study found a relationship between giving colostrum and family support (p=0.029), information sources (p=0.003), behavior (p=0.000). Meanwhile, there was no significance in maternal knowledge (p=.0966), the role of health workers (p=0.836), how to give colostrum (p=0.997) with colostrum. Conclusion: There is a relationship between family support, sources of information and behavior with giving colostrum and there is no relationship between mother's knowledge, the role of health workers and how to give colostrum with giving colostrum.